ANALISIS MEKANIK DAN TERMAL MATERIAL KOMPOSIT BERBASIS SERAT ECENG GONDOK SEBAGAI BAHAN KEMASAN RAMAH LINGKUNGAN - Musliman, Acep; Damayanti, Fitri (JOURNAL ONLINE OF PHYSICS, 2023)
This study aims to analyze the mechanical and thermal properties of water hyacinth fiber-based composite materials as an alternative to environmentally friendly packaging materials. This composite material is produced by mixing water hyacinth fiber with a natural polymer matrix that can decompose easily. Manufacturing methods include mixing, pressing, and thermal treatment processes. The mechanical properties of composite materials, including tensile strength and resistance to deformation, are tested using tensile tests and hardness tests. Thermal analysis is carried out through thermogravimetric tests (TGA) to identify the thermal stability and decomposition of the material. The results showed that the water hyacinth fiber-based composite materials had fairly good mechanical properties in certain mixture compositions, although they were not as strong as composite materials using synthetic fibers. However, this material shows potential in packaging applications that do not require extreme mechanical strength. The mechanical properties of the water hyacinth fiber composite produced lead to the fulfillment of the need for use as packaging, which is light, flexible and not easily broken. The thermal properties of the composites show faster decomposition compared to synthetic fiber based composites, but are still within the acceptable range for single-use packaging. With its environmentally friendly properties, this composite material can be an attractive alternative to reduce the use of plastic in the packaging industry. Nonetheless, improvements in manufacturing processes and material formulations are still required to improve their mechanical and thermal properties and maintain packaging durability under diverse usage conditions.